2020
DOI: 10.1002/pat.4868
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of covalent triazine‐based framework via Friedel‐Crafts reaction of 2,4,6‐trichloro‐1,3,5‐triazine with N,N′‐diphenyl‐N,N′‐di(m‐tolyl)benzidine for capturing and sensing to iodine

Abstract: The covalent triazine-based framework (TDPDB) has been prepared by Friedel-Crafts polymerization reaction of N,N 0 -diphenyl-N,N 0 -di(m-tolyl)benzidine (DPDB) with 2,4,6-trichloro-1,3,5-triazine (TCT) catalyzed by methanesulfonic acid. The yield of the reaction (94.85%) is very high. TDPDB was provided with Brunauer-Emmett-Teller specific surface area of 592.18 m 2 g −1 and pore volume of 0.5241 cm 3 g −1 .TDPDB demonstrated an excellent capacity for capturing iodine (3.93 g g −1 ) and an outstanding ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This result suggested that the electrons of the excited state could be transferred from the energy level orbit of the TMPS to that of the analyzed substance, which leaded to fluorescence quenching 37,38 . In addition, it is well known that if the emission spectrum of the TMPS is the most overlapping with the absorption spectra of a certain analyzed substance, then there will be the greatest possibility that the energy transfer will occur between them 30,34 . Therefore, the fluorescence emission spectrum of TMPS in THF and the UV–Vis absorption spectra of NACs in THF are drawn, respectively, which can be seen that the TMPS and DNP possess the largest overlapping areas, which almost do not overlap with several other NACs, that once again demonstrate the high efficiency of TMPS in fluorescence sensing of DNP (Figure 7D).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This result suggested that the electrons of the excited state could be transferred from the energy level orbit of the TMPS to that of the analyzed substance, which leaded to fluorescence quenching 37,38 . In addition, it is well known that if the emission spectrum of the TMPS is the most overlapping with the absorption spectra of a certain analyzed substance, then there will be the greatest possibility that the energy transfer will occur between them 30,34 . Therefore, the fluorescence emission spectrum of TMPS in THF and the UV–Vis absorption spectra of NACs in THF are drawn, respectively, which can be seen that the TMPS and DNP possess the largest overlapping areas, which almost do not overlap with several other NACs, that once again demonstrate the high efficiency of TMPS in fluorescence sensing of DNP (Figure 7D).…”
Section: Resultsmentioning
confidence: 95%
“…The FT‐IR of TMPS is shown in Figure 1, the diffraction peaks around 1545 cm −1 , 1454 (C=N) and 1381 cm −1 (C‐N) are attributed to the characteristic diffraction peaks of the triazine ring in the network. Further comparison of the FT‐IR of TMPS to TCT shows that peaks at 847 cm −1 in TCT do not present in TMPS (Figure 1), which implied a complete reaction between the two monomers 30 . The strong stretching vibration peak at 1125 cm −1 in Figure 1 is due to the Si‐O‐Si bond, which indicate that the original siloxane skeleton remains in after polymerization of the two monomers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The trace amounts of iodine, whether is residual in the products or is decomposed from iodine‐containing compounds, will affect the quality of the product and cause serious harm, especially food and drugs. Even the presence of a spot of molecular iodine in the drug can have a disastrous impact on human health, it is necessary to thoroughly control the iodine content during the preparation and reserve of iodine containing drugs 50–52 . The fluorescent CMPs, with the conjugated structure throughout the networks and the inherent porosity, are the most promising platforms for the detection of both NACs and iodine 50–53 …”
Section: Introductionmentioning
confidence: 99%
“…Even the presence of a spot of molecular iodine in the drug can have a disastrous impact on human health, it is necessary to thoroughly control the iodine content during the preparation and reserve of iodine containing drugs. [50][51][52] The fluorescent CMPs, with the conjugated structure throughout the networks and the inherent porosity, are the most promising platforms for the detection of both NACs and iodine. [50][51][52][53] In this paper, we chosen a simple thiophene derivative,…”
Section: Introductionmentioning
confidence: 99%